Blue light combined with salicylic acid treatment maintained the postharvest quality of strawberry fruit during refrigerated storage - Yunting Zhang; Shanlin Li; Meiyi Deng; Rui Gui; Yongqiang Liu; Xinpeng Chen; Yuanxiu Lin; Mengyao Li; Yan Wang; Wen He; Qing Chen; Yong Zhang; et al. (Food Chemistry: X, 2022)
Strawberry is a high economic and nutritional value fruit, but marketing is limited by a short postharvest life. The objective of this work is to assess the influence of blue light (BL) and salicylic acid (SA, 2 mM) on strawberry postharvest quality during cold storage. The results showed that the combination of BL and SA noticeably delayed weight loss, prevented decay, improved fruit skin brightness, and increased soluble protein. Strawberries treated with BL + SA had lower total soluble solids and titratable acidity contents among treatments but had no significant change during the entire storage. Additionally, contents of total flavonoids, phenolics, anthocyanins and proanthocyanidins, activities of superoxide dismutase (SOD) and ascorbate peroxidase (APX) and total antioxidant capacities in BL + SA-treated fruit were kept at stable levels throughout the entire storage. Collectively, these findings suggest that BL + SA treatment exhibits a high potential in maintaining postharvest fruit quality of strawberry fruit.